Programa de Seguridad para Trabajos en Espacios Confinados para la Empresa Constructora Bilco - Rivera-Paniagua, Ana Lucía (Instituto Tecnológico de Costa Rica, 2017)
The project was developed in the construction company Bilco S.A., located in San Rafael de Escazú. Its purpose is to address the critical situation presented by the construction company in the subject of confined spaces, specifically, tanks as a result of the evaluation and prioritization of risks that the company made last year by topics. For the analysis of the current situation of the company, different tools were used, such as a checklist for hazard identification, atmospheric monitoring, risk matrix, OSHA-based checklist, interviews, surveys, FODA matrix, CAME matrix , and as a complement a meeting with experts was held. It was determined that the work inside the tanks represents an extremely high risk for the company, mainly due to the atmospheric conditions to which the workers are exposed and the lack of essential equipment to perform a safe task. The organization has little time to invest in the area of occupational health in a planned manner, therefore, it is concluded that management on the issue of confined spaces is deficient and constitutes the main problem in terms of security. For the above reasons, the need arises for a security program for works in confined spaces for Bilco construction company, where engineering designs such as signage, enclosures and forced ventilation systems are contemplated. In addition, administrative controls from safe work procedure, rotation of positions and training plan for both indirect and direct workers. With the implementation of these measures, the aim is to improve security in the execution of works in confined spaces.
Proyecto de Graduación (Bachillerato en Ingeniería en Seguridad Laboral e Higiene Ambiental) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Seguridad Laboral e Higiene Ambiental, 2017.
Keywords: Factores de riesgo; Condiciones; Construcción; Seguridad ocupacional; Trabajadores; Research Subject Categories::MEDICINE::Social medicine::Public health medicine research areas::Occupational medicine